Genetic evaluation of ESBL-producing Escherichia coli urinary isolates in Otago, New Zealand. Issue 4 (10th November 2021) - Hapuarachchi, Isuri U; Hannaway, Rachel F; Roman, Tabatha; Biswas, Ambarish; Dyet, Kristin; Morgan, Xochitl; Ussher, James E
Abstract: Objectives: The incidence of infections with ESBL-producing Escherichia coli (ESBL-Ec) in New Zealand is increasing. ESBL-Ec most commonly cause urinary tract infections and are seen in both community and hospitalized patients. The reason for the increasing incidence of ESBL-Ec infections is unknown. Methods: In this study, 65 urinary ESBL-Ec isolates from the Otago region in 2015 were fully genetically characterized to understand the mechanisms of transmission. The ESBL gene, E. coli STs, plasmid types and genetic context (e.g. insertion sequences) of ESBL genes were determined by a combination of whole genome and plasmid sequencing. The phylogenetic relationships of the isolates were compared with ESBL-Ec isolates sequenced as part of the 2016 nationwide survey. Results: Significant diversity of E. coli strains, plasmids, and the genetic context of ESBL genes was seen. However, there was evidence of common mobile genetic elements in unrelated ESBL-Ec. Conclusions: Multiple introductions of ESBL resistance genes or resistant bacterial strains with limited horizontal transmission of mobile genetic elements accounts for the increased incidence of ESBL-Ec in this low prevalence area. Future studies should investigate modes of transmission of ESBL-Ec in the Otago region.